Nerve infiltration anesthesia of tongue in cattle - ΔΗΜΗΤΡΙΑΔΗΣ, Ι.; ΜΠΡΟΒΑΣ, Δ. (Journal of the Hellenic Veterinary Medical Society, 2019)
For a painless and easy operation on the tongue as it is required during the experimental intralingual inoculation of Foot-and-Mouth Disease virus in cattle the infiltration by anesthetic of the tongue motor and sensory nerves is suggested. The anesthetic used was Xylocain 2% added with Adrenalin. Except a few and non significant mechanical wounding of the tongue no other side effects were observed. The anesthesia was complete in 14 out of 15 animals used, that is in a percentage of 93.3.